1997
DOI: 10.1056/nejm199705013361803
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Pancreatic-Enzyme Supplements and Fibrosing Colonopathy in Children with Cystic Fibrosis

Abstract: In young children with cystic fibrosis, we found a strong relation between high daily doses of pancreatic-enzyme supplements and the development of fibrosing colonopathy. Our findings support recommendations that the daily dose of pancreatic enzymes for most patients should remain below 10,000 units of lipase per kilogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(143 citation statements)
references
References 20 publications
5
125
0
4
Order By: Relevance
“…47 A similar US study found only the dose of lipase to be a factor. 48 The age of the patient, the clinician's view on the importance of the copolymer Eudragit L30 D55 (in the coating of some preparations) as a factor causing FC (see below), the dose of enzyme that is required to control malabsorption, the cost, and local availability will also influence which preparation is used.…”
Section: Choice Of Pancreatic Enzyme Preparationmentioning
confidence: 99%
“…47 A similar US study found only the dose of lipase to be a factor. 48 The age of the patient, the clinician's view on the importance of the copolymer Eudragit L30 D55 (in the coating of some preparations) as a factor causing FC (see below), the dose of enzyme that is required to control malabsorption, the cost, and local availability will also influence which preparation is used.…”
Section: Choice Of Pancreatic Enzyme Preparationmentioning
confidence: 99%
“…However, it has been shown that an increase in the dose of pancreatic enzymes does not completely correct fat malabsorption (13). In addition, the use of high-strength pancreatic enzyme supplements to increase lipolysis has been reported to be associated with fibrosing colonopathy (14)(15)(16)). …”
Section: Introductionmentioning
confidence: 99%
“…Because of exocrine PI, CF patients depend on pancreatic enzyme supplements. However, the use of high doses of pancreatic enzymes does not always normalize fat absorption and may lead to fibrosing colonopathy (51). This led to an interest in increasing the level of gastric lipase (the only endogenous digestive lipase not affected by CF) by nutritional adaptation as previously reported in animals (24 -27) and in healthy adults (28).…”
Section: Discussionmentioning
confidence: 99%